Brooke's quest for captain - Jones, Jen (North Mankato, Minn Stone Arch Books, 2012)
Brooke Perrino really wants to be captain of her school cheerleading team, but she is having trouble with eighth-grade algebra and suddenly she is beginning to doubt her ability to handle the pressure
A gift from book Africa
English Stories
1 2 13 15
NEW_ZTN_GN
Keywords: Cheerleading -- Fiction; Middle schools -- Fiction